2021
DOI: 10.3389/fonc.2021.760697
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Manifestation of a Presumed Non-Osteophilic Brain Neoplasm: Extensive Axial Skeletal Metastases From Glioblastoma With Primitive Neuronal Components

Abstract: BackgroundGlioblastoma multiforme (GBM) is the most common malignant tumor of the central nervous system. GBM with primitive neuronal component (GBM-PNC) is an aggressive variant identified in 0.5% of GBMs. Extracranial metastasis from GBM-PNC is a rare and challenging situation.MethodsA special case of early-onset GBM with systemic bone metastasis was enrolled. Clinical data, including patient characteristics, disease course, and serial radiological images were retrieved and analyzed. Tumor tissues were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Compared with GBM researches, gene data of GBM with ECM are limit. Similar to previous studies (8)(9)(10)(11), TP53 and PTEN mutations in ECM lesion were identified in the patient. Despite the role of genetic mutations in GBM with ECM is still not fully clear, ongoing research on this topic will ultimately implement a personalized or precision medicine for this deadly disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Compared with GBM researches, gene data of GBM with ECM are limit. Similar to previous studies (8)(9)(10)(11), TP53 and PTEN mutations in ECM lesion were identified in the patient. Despite the role of genetic mutations in GBM with ECM is still not fully clear, ongoing research on this topic will ultimately implement a personalized or precision medicine for this deadly disease.…”
Section: Discussionsupporting
confidence: 90%
“…Great progress has recently been made in the genomic analysis of GBM tumorigenesis and recurrence. However, after a systematic search on PubMed and Google Scholar, genomic features of GBM with ECM was found in 5 reports (Table 1) (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Each detected mutation has been described previously in various tumors (c.2259G>A in myelodysplastic syndrome 15 , c.2119G>A in GB 6 , c.1502A>G and c.1661G>A in acute myeloid leukemia 16 , 17 ). DNMT3A mutations are well-known prognostic factors in acute myeloid leukemia 18 , but only sporadic occurrence has been reported in gliomas 6 , 19 21 . Considering previous observations showing ALT-related phenotypes in DNMT-deficient cells 22 , the cooperation of ATRX and DNMT3A mutations in telomere length maintenance can be suspected.…”
Section: Discussionmentioning
confidence: 99%
“…Among the few reports that have conducted genomic analyses in patients with GB and extra-CNS metastases, mutations in TP53 have been the most frequently reported (6,12,(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…As this case and prior reports demonstrate, recurrent GB with extra-CNS metastases has very few treatment options. Exceptions to this rule are regional relapses such as those occurring in the dura and head and neck LN, or in oligometastatic bone metastases, which various reports have shown that may be subjected to local treatments achieving longer local and systemic controls (10,11,15,26). Considering that systemic therapy has not demonstrated to prolong OS in patients with recurrent GB, its management is even more complex in patients with extra-CNS metastases.…”
mentioning
confidence: 99%